Cost‐Effectiveness Analysis of Adjuvant Alectinib versus Platinum‐Based Chemotherapy in Resected ALK‐Positive Non‐Small‐Cell Lung Cancer in the Chinese Health Care System - Qiran Wei; Yifang Liang; Jiahui Mao; Xin Guan (Cancer Medicine)
ABSTRACT Objectives The ALINE trial demonstrated the superiority of alectinib over platinum‐based chemotherapy in resected Anaplastic Lymphoma Kinase (ALK)‐positive non‐small‐cell lung cancer (NSCLC). Considering the high cost of alectinib, this study aimed to evaluate the economic value of alectinib compared to platinum‐based chemotherapy for treating early‐stage ALK‐positive NSCLC from the perspective of the Chinese health care system. Materials and Methods We developed a five‐state Markov model with monthly cycles to estimate the lifetime costs, life‐years (LYs), quality‐adjusted life‐years (QALYs), and incremental cost‐effectiveness ratios (ICERs) in terms of cost per LY gained and per QALY gained. Costs were obtained from database, expert opinions and published literature, and utilities were primarily derived from a multicenter cross‐sectional study based on the Chinese population. Costs and outcomes were discounted at 5% per year. Sensitivity analyses and scenario analyses were conducted to assess uncertainty in model results. Results Compared to platinum‐based chemotherapy, alectinib increased total costs by $16,245 and provided gains of 2.02 LYs and 1.84 QALYs over a lifetime horizon. ICERs were $8,052/LY and $8,806/QALY. The ICER in terms of cost per QALY gained was most sensitive to the outcome discount rate. Probabilistic sensitivity analysis indicated a 93% probability of alectinib being cost‐effective at a willing‐to pay (WTP) threshold of $12,367/QALY (1 GDP per capita), rising to 100% at $37,100/QALY (3 GDP per capita). Conclusion Alectinib appears to be the preferred cost‐effective option in the adjuvant treatment for Chinese patients with resected early‐stage ALK‐positive NSCLC.